A Multimodal Discourse Analysis in Roma Biscuit Advertisement - Lioni, Shilva; Zinta, Preity; Nuha, Najwa Ulin (LingoLitera, 2026)
The increasing influence of the Korean Wave (Hallyu) has significantly reshaped advertising strategies in Indonesia, where Korean celebrities are frequently employed as brand ambassadors to strengthen consumer engagement and emotional appeal. This study investigates the multimodal construction of emotional meaning in the Roma Kelapa television advertisement featuring the Korean actor, Lee Min Ho. Employing a qualitative descriptive approach, the study adopts Multimodal Discourse Analysis (MDA) based on the framework of Kress and van Leeuwen to analyze the interplay of linguistic, visual, gestural, and auditory modes. The data consist of a 30-second Roma Kelapa advertisement, with analysis focusing on verbal expressions, written text, gaze, facial expressions, gestures, camera techniques, color composition, and product representation. The findings reveal that emotional meaning is not produced by a single communicative mode but emerges from the integration of verbal and non-verbal semiotic resources. Linguistically, evaluative slogans and conversational expressions position Roma Kelapa as a symbol of appreciation, family affection, and product excellence. Visually, direct gaze, warm facial expressions, close-up shots, harmonious color schemes, and culturally recognizable celebrity imagery foster intimacy, trust, and authenticity. Furthermore, Lee Min Ho's public persona functions as a multimodal semiotic resource that enhances the advertisement's persuasive and emotional impact within the Indonesian cultural context.